2019
DOI: 10.17675/2305-6894-2019-8-4-12
|View full text |Cite
|
Sign up to set email alerts
|

Barite crystallization in presence of novel fluorescent-tagged antiscalants

Abstract: Formation of barite crystals in a bulk supersaturated aqueous solution at ambient temperature is studied in presence of two novel fluorescent-tagged antiscalants: a bisphosphonate 1-hydroxy-7-(6-methoxy-1,3-dioxo-1H-benzo[de]isoquinolin-2(3H)-yl)heptane-1,1-diyldi-(phosphonic acid), HEDP-F, and a co-polymer of N-allyl-4-methoxy-1,8-naphtalimide with acrylic acid, PAA-F1 by fluorescent microscopy, scanning electron microscopy (SEM), turbidimetry, dynamic light scattering (DLS) and a particle counter technique. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 37 publications
3
4
0
Order By: Relevance
“…However, the visualization of PAA-F1 molecules indicates clearly that there is no definite interaction between antiscalant and gypsum along the brine RO treatment. The same result was obtained earlier for HEDP-F/gypsum RO desalination process [22] as well as for batch static experiments with gypsum [20] and barite [21] in presence of HEDP-F. A tentative mechanism of gypsum inhibition in RO membrane fouling is proposed [22] and our present data for PAA-F1 give a further approval to this hypothesis.…”
Section: Tentative Mechanism Of Gypsum Membrane Fouling Inhibition Bysupporting
confidence: 92%
See 4 more Smart Citations
“…However, the visualization of PAA-F1 molecules indicates clearly that there is no definite interaction between antiscalant and gypsum along the brine RO treatment. The same result was obtained earlier for HEDP-F/gypsum RO desalination process [22] as well as for batch static experiments with gypsum [20] and barite [21] in presence of HEDP-F. A tentative mechanism of gypsum inhibition in RO membrane fouling is proposed [22] and our present data for PAA-F1 give a further approval to this hypothesis.…”
Section: Tentative Mechanism Of Gypsum Membrane Fouling Inhibition Bysupporting
confidence: 92%
“…It is demonstrated that the fluorescent-tagged antiscalants may become very powerful tools in membrane scaling inhibition studies.However, in spite of numerous relevant studies, some controversy regarding both the dominant scaling mechanism in particular situations and the mechanism of antiscalant activity still exists [12][13][14][15][16][17][18]. Recent reviews on scale formation control in RO technologies [6,19] mention two main hypothetic mechanisms of inhibition: (i) antiscalant molecules adsorb on the active growth sites at the crystal surface of sparingly soluble inorganic salt and retard nucleation and crystal growth by distorting its crystal structure; (ii) antiscalant molecules provide similar electrostatic charge, and thus, repulsion between particles prevents them from agglomeration.Nevertheless, our recent static [20,21] and RO [22] experiments operating gypsum as a model scale in presence of a novel fluorescent-tagged bisphosphonate antiscalant 1-hydroxy-7-(6-methoxy-1,3dioxo-1H-benzo[de]isoquinolin-2(3H)-yl)heptane-1,1-diyl-bis(phosphonic acid), HEDP-F (H 4 hedp-F) revealed a paradoxical effect: an antiscalant does not interact with gypsum at all, but provides nevertheless retardation of corresponding deposit formation. According to the classical crystallization theory [23], this is possible only in the case, when gypsum passes bulk heterogeneous nucleation, and exactly the "nanodust" plays the role of the solid phase template.…”
mentioning
confidence: 93%
See 3 more Smart Citations